Milk Fouling Simulation in a Triple Tube Heat Exchanger - Ansari, Md. I.A.; Sahoo, P K; Datta, A K (Journal of Agricultural Engineering, 2013)
Milk fouling in heat exchanger causing an increased resistance to heat transfer and reduced performance is acommon phenomenon during milk processing at Ultra-High-Temperature (UHT). A mathematical model wasformulated for triple tube heat exchanger using hydrodynamics and heat balance concept. The model wassimulated using a numerical technique based on the method of characteristics. Modified Eulerâ€™s technique wasused to solve differential equations using a computer programme. The model predicted with time both thefouling behaviour and bulk milk temperature along the length of the heat exchanger. At an early period ofoperation, uniform fouling deposit occurred throughout the length of the heat exchanger due to constant heatexchanger wall temperature. The equilibrium value of fouling deposit was found to be 0.84 mm for the insidetube and 0.61 mm for the middle tube. The fouling thickness was stabilized after about 50 min. The bulk milktemperature at the end of simulation was found to be 148 ÂºC. The results can be used to develop a controlsystem to get target product temperature and optimal operating strategies.